Latin American Cities in the Eighteenth Century: A Sketch - Borah, Woodrow (Urban History Review / Revue d'histoire urbaine, 1980)
In Latin America the eighteenth century was a time of approximate doubling of the population and considerable economic development and reorientation of the economy. Urban settlement reflected these changes. The bulk of urban growth was by replication of existing patterns into areas of new settlement. Some expansion of older cities and heightening of urban functions took place. In the reordering of regional economies, Buenos Aires, Havana, and Rio de Janeiro profited; Lima failed to prosper. Within existing and new cities, much building replaced older structures in more durable materials, and, in the largest, multi-family, multi-storied structures appeared. Following developments in Europe, beginnings were made in paving streets, providing lighting, installing drains, and so-forth. In similar wise, administration adopted new forms and social welfare was reorganized for more efficient response to natural disasters. Cultural models, copied from Europe, even included the beginning of cafés.